A study on factors influencing employee performance in human resource and administration department at BERNAMA / Siti Aisyah Noraziman - Noraziman, Siti Aisyah (2010)
This study is design to study the factors influencing employee performance in Human Resource and Administration Department at BERNAMA. The problems that arise in whether employee satisfied with the appraisals conducted in the organization and also either if they are committed in the organization. The researcher used employee performance as the dependent variable while job satisfaction and organizational commitment as the independent variable. Moreover, the methods that been used are questionnaire among the employee in Human Resource and Administration Department at BERNAMA in order to identify the relevant information regarding to the research. The research also used the secondary data such as journals articles, previous thesis and also internal data. Furthermore, researcher used stratified sampling technique which is the simple random sampling to gain information regarding this research. Hence that, the findings from the study found that, there is no significant relationship between job satisfaction on employee performance in Human Resource and Administration Department at BERNAMA while there is a significant relationship between organizational commitment on employee performance in Human Resource and Administration Department at BERNAMA. Thus, there are several recommendation should be taken by BERNAMA. Firstly, BERNAMA should enhance the training program more dynamically and innovative in the organization so that employees can increase their knowledge and competencies. Secondly, top level management of BERNAMA should enhance employability in the organization. This can increase the employee motivation to work more efficiently and effectively.